Updated checklist of the reptiles from Loreto Department - Aguilar, César A. (2021)
This paper presents an updated list of the reptiles occurring in the Department of Loreto, Perú including information on conservation status, endemic species and areas with information gaps. Herpetological literature, databases and the collection of the Department of Herpetology of the Natural History Museum of the National University of San Marcos were used to update the species list. A total of 182 species were recorded, with squamates (lizards and snakes) representing 90% of reptiles in Loreto. Only one species, Helicops yacu, is endemic to Loreto and Dipsas peruana is the only species with an altitudinal distribution above 500 m. Six species are in IUCN threatened categories. Six and four species are in threatened and near threatened national categories respectively. Mayor information gaps are observed in areas near the borders with Brazil and Colombia.